Using Technology in English Teaching of Pre-Service Teachers in 4.0 Industrial Revolution Era - Maria Yosephin Widarti Lestari; Siti Musarokah; Asysyifa Dinar Prashanty (Universitas PGRI Semarang, 2020)
The study aims at knowing the use of technology in teaching learning process of pre-service teachers of English Study Program of Universitas PGRI Semarang. The subjects of the study are the eight semester students which are Pre-service teachers of the English Study Program of Universitas PGRI Semarang in the academic year 2018/2019. The instrument used in the study is questionnaire. The techniques used in the study are sharing the questionnaire to the eight semester students through WhatsApp to know what kinds of technology used by them are and interview to know how their perception of the use of technology in teaching learning process is. The qualitative data are analyzed by reducing the data, classifying the data and drawing conclusion. The result of the study shows that Pre-service teachers tend to use same kinds of technology in teaching learning process, and they have an opinion that technology is really important for the teachers and for students.